Brave new Arctic : the untold story of the melting North - Serreze, Mark C. (Science essentials (National Academy of Sciences (U.S.)), 2018)
An insider account of how researchers unraveled the mystery of the thawing ArcticIn the 1990s, researchers in the Arctic noticed that floating summer sea ice had begun receding. This was accompanied by shifts in ocean circulation and unexpected changes in weather patterns throughout the world. The Arctic's perennially frozen ground, known as permafrost, was warming, and treeless tundra was being overtaken by shrubs. What was going on? Brave New Arctic is Mark Serreze's riveting firsthand account of how scientists from around the globe came together to find answers. In a sweeping tale of discovery spanning three decades, Serreze describes how puzzlement turned to concern and astonishment as researchers came to understand that the Arctic of old was quickly disappearing--with potentially devastating implications for the entire planet. Serreze is a world-renowned Arctic geographer and climatologist who has conducted fieldwork on ice caps, glaciers, sea ice, and tundra in the Canadian and Alaskan Arctic. In this must-read book, he blends invaluable insights from his own career with those of other pioneering scientists who, together, ushered in an exciting new age of Arctic exploration. Along the way, he accessibly describes the cutting-edge science that led to the alarming conclusion that the Arctic is rapidly thawing due to climate change, that humans are to blame, and that the global consequences are immense. A gripping scientific adventure story, Brave New Arctic shows how the Arctic's extraordinary transformation serves as a harbinger of things to come if we fail to meet the challenge posed by a warming Earth.